2021
DOI: 10.3390/nu13041081
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sports Nutrition Knowledge in Elite Gaelic Footballers

Abstract: Nutrition intake plays a crucial role in improving athletic performance, enhancing adaptations to training, and augmenting recovery from exercise. However, research has reported that Gaelic footballers consistently fail to meet energy and carbohydrate recommendations. Sports nutrition knowledge (SNK) can influence the dietary intake of athletes, and therefore has the potential to have a significant impact on athletic performance. The aim of this study was to investigate the current level of SNK in elite Gaelic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 46 publications
0
20
1
Order By: Relevance
“…Previous studies found significant differences in knowledge scores based on sex [ 5 , 8 , 26 ], BMI classification [ 26 ], and sports category [ 26 ], which we did not observe in this study. While the general principle of sports nutrition is universal for all athletes worldwide, different studies used different sets of questions and assessed different knowledge domains.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies found significant differences in knowledge scores based on sex [ 5 , 8 , 26 ], BMI classification [ 26 ], and sports category [ 26 ], which we did not observe in this study. While the general principle of sports nutrition is universal for all athletes worldwide, different studies used different sets of questions and assessed different knowledge domains.…”
Section: Discussioncontrasting
confidence: 99%
“…Nutritional knowledge is a modifiable factor influencing dietary behaviours. Athletes’ understanding of sports nutrition can thus influence their food choices, which in turn can affect their overall athletic performance [ 5 , 6 ]. Hence, athletes should obtain appropriate nutritional information from a credible and certified source, as this will shape their understanding of nutrition [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the measurement tool we used in this study questionnaire included all the subsections recommended by a recent systematic review [38]. Studies that compared nutrition subsections similar to ours found that scores were better in the sports nutrition knowledge compared to the general nutrition knowledge section [39,40].…”
Section: Discussionmentioning
confidence: 93%
“…Research has consistently shown sub-optimal dietary practices amongst elite and sub-elite male Gaelic team sport athletes, most notably failure to meet both energy and carbohydrate requirements. Gaelic football players dietary intake has been identified as inadequate to meet recommendations, with average energy deficits of 12.3% per day [95], carbohydrate intakes of 3.4-3.7 g kg day −1 [95][96][97] lower than minimum recommendations of 5 g kg day −1 . It remains to be established if similar dietary intakes are adopted by female Gaelic team sport athletes, however similar findings have been reported with other female field-based team sport athletes [98][99][100].…”
Section: Energy and Macronutrient Intakementioning
confidence: 99%
“…Despite a current lack of dietary investigation within the population, other female team sport athletes with poor nutritional knowledge have been shown have insufficient energy and carbohydrate intake [98,99]. Similarly, this relationship between poor nutritional knowledge and sub-optimal dietary intake has been seen in male Gaelic football players [95,97]. As such it would be beneficial to measure dietary intake and assess nutritional knowledge simultaneously in elite female Gaelic team sport athletes to see if knowledge translates to practice.…”
Section: Nutritional Knowledgementioning
confidence: 99%